2019
DOI: 10.1002/ceat.201800728
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Blending of Non‐Newtonian Fluids in Static Mixers by Planar Laser‐Induced Fluorescence and Electrical Resistance Tomography

Abstract: Planar laser-induced fluorescence (PLIF) and electrical resistance tomography (ERT) were applied simultaneously to monitor the mixing performance of a KM static mixer for the blending of non-Newtonian fluids of dissimilar rheologies in the laminar regime. The areal distribution method was used to obtain quantitative information from the ERT tomograms and the PLIF images. Comparison of the ERT and PLIF results demonstrates the ability of ERT to detect the mixing performance in cases of poor mixing within the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Although mixing in general has always been a major area of academic and industrial interest, liquid-liquid mixing in particular poses the highest challenges, making it one of the least understood mixing mechanisms despite the large existing literature on it [Afshar Ghotli et al, 2013. Nowadays, this type of mixing can be extensively found in multiple industrial applications such as (petro) chemical, mineral processing, personal care and home products, pharmaceutical, and food in the form of immiscible liquidliquid dispersions [Castellano et al, 2018, Gao et al, 2016, emulsions [Gallo-Molina et al, 2017, Wong et al, 2015, Tadros, 2013 and miscible blending of non-Newtonian fluids [Alberini et al, 2014, Forte et al, 2019b. Emulsions are arguably the most noteworthy systems in this category due to their inherent complexity and recurrent appearance in the aforementioned industries.…”
Section: Introductionmentioning
confidence: 99%
“…Although mixing in general has always been a major area of academic and industrial interest, liquid-liquid mixing in particular poses the highest challenges, making it one of the least understood mixing mechanisms despite the large existing literature on it [Afshar Ghotli et al, 2013. Nowadays, this type of mixing can be extensively found in multiple industrial applications such as (petro) chemical, mineral processing, personal care and home products, pharmaceutical, and food in the form of immiscible liquidliquid dispersions [Castellano et al, 2018, Gao et al, 2016, emulsions [Gallo-Molina et al, 2017, Wong et al, 2015, Tadros, 2013 and miscible blending of non-Newtonian fluids [Alberini et al, 2014, Forte et al, 2019b. Emulsions are arguably the most noteworthy systems in this category due to their inherent complexity and recurrent appearance in the aforementioned industries.…”
Section: Introductionmentioning
confidence: 99%
“…• Development of flexible and smart manufacturing technologies so that manufacturing plants can be "re-tooled" to produce multiple products and change production (Kang et al, 2016) as preferences and desires from the outer layer change. Concepts such as disposable reactors (Glindkamp et al, 2009), micro reactors (Rossetti and Compagnoni, 2016) as well as non-invasive measurement techniques such as image analysis (Forte et al, 2019) and tomography (Tapp et al, 2003) currently under development in the inner layer could enable this movement. • Innovative and efficient processing through intensification that can significantly reduce the energy and resource demand are concepts that are already developed (Tian et al, 2018), but their industrial implementation need to increase.…”
Section: Researchmentioning
confidence: 99%
“…Applications of slicing (or cutting) droplets are mainly found in microfluidics [7] and also -on a larger scale -in static mixers. [8] Forte et al [9] investigated the fundamental mechanisms of oil droplet breakup in static mixers. They found that the drop size decreased to a critical point, when the continuous phase (water) flow rate was increasing.…”
Section: Introductionmentioning
confidence: 99%